Developing cost models for wages of construction workers of civil engineering in Singapore - Xie, Daidong (2008)
The aim of this study is to explore cost models for predicting wages of construction workers of civil engineering in Singapore exploiting the multiple regression method. On basis of the economy theory concerning the demand and supply of goods and services, the conceptual models have been developed, indicating that the wages of construction workers are determined by the interaction of general economic situations, construction market and construction labor market.